Alpinetin Suppresses Zika Virus-Induced Interleukin-1β Production and Secretion in Human Macrophages - Nitwara Wikan; Saranyapin Potikanond; Phateep Hankittichai; Phatarawat Thaklaewphan; Sathit Monkaew; Duncan R. Smith; Wutigri Nimlamool (MDPI AG, 2022)
Zika virus (ZIKV) infection has been recognized to cause adverse sequelae in the developing fetus. Specially, this virus activates the excessive release of IL-1β causing inflammation and altered physiological functions in multiple organs. Although many attempts have been invested to develop vaccine, antiviral, and antibody therapies, development of agents focusing on limiting ZIKV-induced IL-1β release have not gained much attention. We aimed to study the effects of alpinetin (AP) on IL-1β production in human macrophage upon exposure to ZIKV. Our study demonstrated that ZIKV stimulated IL-1β release in the culture supernatant of ZIKV-infected cells, and AP could effectively reduce the level of this cytokine. AP exhibited no virucidal activities against ZIKV nor caused alteration in viral production. Instead, AP greatly inhibited intracellular IL-1β synthesis. Surprisingly, this compound did not inhibit ZIKV-induced activation of NF-κB and its nuclear translocation. However, AP could significantly inhibit ZIKV-induced p38 MAPK activation without affecting the phosphorylation status of ERK1/2 and JNK. These observations suggest the possibility that AP may reduce IL-1β production, in part, through suppressing p38 MAPK signaling. Our current study sheds light on the possibility of using AP as an alternative agent for treating complications caused by ZIKV infection-induced IL-1β secretion.